Price setting behaviour in Spain: evidence from micro PPI data - Luis J. Álvarez; Pablo Burriel; Ignacio Hernando (European Central Bank (ECB), 2005)
This paper identifies the basic features of price setting behaviour at the producer level in the Spanish economy using a large dataset containing the micro data underlying the construction of the PPI over the period 1991-1999. It explores how these general features are affected by some specific factors (cost structure, degree of competition, demand conditions, government intervention, level of inflation, seasonality, and the practice of using attractive prices) and presents a comparison of price setting practices at the producer and at the consumer level to ascertain whether the retail sector augments or mitigates price stickiness. We find that prices do not change often but do so by a large amount. The cost structure, proxied by the labour share and the relevance of raw materials, and the degree of competition, proxied by import penetration, affect price flexibility. We also find some evidence that producer prices are more flexible than consumer prices.
Keywords: E31; D40; 330; frequency of price changes; price setting; producer prices; Preisniveau; Verbraucherpreisindex; Spanien